CALCULATION OF THE CONCENTRATIONS OF METHANE CH4 , CARBON MONOXIDE CO AND SULFUR DIOXIDE SO2 IN THE URBANIZED AREA OF BISHKEK (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article describes a photochemical model in the troposphere, where the vertical turbulent transport is taken into account and the horizontal parametrization of the transport is carried out. The photochemical processes that affect pollution in urban areas and the free troposphere are considered in detail.
Keywords: concentration, harmful gases, methane, carbon monoxide, sulfur dioxide, variation, photochemistry.